2012
DOI: 10.1007/7854_2012_215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Enrichment Exposure on Synaptic Transmission and Plasticity in the Hippocampus

Abstract: Exposure to an enriched environment (EE) is beneficial to the structure and function of the brain. The added sensory, social, and spatial complexity of the EE also improves cognitive functions such as memory in both healthy brains and damaged or diseased brains, yet the underlying neural mechanisms of these cognitive improvements are poorly understood. In particular, studies that have examined the effects of EE on cellular function in the hippocampus, a structure critical for memory storage, have produced some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 86 publications
4
40
0
2
Order By: Relevance
“…In addition, Amaral et al [2] reported that reduced locomotion behavior in an open field persisted after a prolonged (8 weeks), but not after a shorter (4 weeks), housing duration. This discrepancy between the effect of EE on the physiological properties and on the behavioral measures has recently been pointed out by Eckert and Abraham [10]. They suggest that initially heightened excitability and synaptic plasticity might return to baseline levels through a homeostatic mechanism, while other more subtle mechanisms underlie long lasting behavioral effects.…”
Section: Environmental Enrichment Increased Cellular Excitability In mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Amaral et al [2] reported that reduced locomotion behavior in an open field persisted after a prolonged (8 weeks), but not after a shorter (4 weeks), housing duration. This discrepancy between the effect of EE on the physiological properties and on the behavioral measures has recently been pointed out by Eckert and Abraham [10]. They suggest that initially heightened excitability and synaptic plasticity might return to baseline levels through a homeostatic mechanism, while other more subtle mechanisms underlie long lasting behavioral effects.…”
Section: Environmental Enrichment Increased Cellular Excitability In mentioning
confidence: 96%
“…While increased intrinsic excitability was observed after a relatively short duration of enrichment (<35 days; [35]), this was not the case in another study which used a longer duration (8 weeks; [9]). Interestingly, it has recently been pointed out in a review article, that enhanced synaptic properties and population spike induction by environmental enrichment, were mostly observed in studies with a relatively short housing duration (<4 weeks; [10]). However, a systematic study of the effect of housing duration on intrinsic cellular excitability has not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…For example, exercise reduces the incidence of obesity-related diseases, at least in part, by altered lipoprotein levels (Ainslie et al, 2005;Craig et al, 1996). In contrast, the ability of physical activity to enhance learning during development may be mediated by the proliferation of glial and endothelial cells, as well as an increases in neurogenesis and neuronal connectivity, in brain regions critical for learning and memory (Eckert and Abraham, 2013;Gelfo et al, 2009;Mandyam et al, 2007;Viola et al, 2009).…”
mentioning
confidence: 88%
“…Recent studies suggest that enriching life experiences, such as higher education, increase memory and learning formation (Bennett, McRae, Levy, & Frick, 2006;Bousiges et al, 2010;Eckert & Abraham, 2012;Leal-Galicia, Castañeda-Bueno, Quiroz-Baez, & Arias, 2008;Patel, 2012) and that higher education and occupational attainment may decrease the risk of Alzheimer's dementia, possibly because of greater cognitive reserve that may delay clinical manifestations (e.g., Stern, 2012;Stern et al, 1994;Valenzuela & Sachdev, 2006). Education/literacy may, to some degree, strengthen neural redundancy and perhaps play a role in delaying clinical manifestations, such as phonologic errors, or rate of progression in LPA.…”
Section: Petroi Et Almentioning
confidence: 99%